Russia’s Petroleum Industry in the Period of Sanctions and COVID-19 Pandemic: A Review and Analysis - Saiymova, Meiramkul; Baikadamov, Nurken; Tyurina, Yuliya; Kutsuri, Georgiy; Sanginova, Lola; Troyanskaya, Marija (International Journal of Energy Economics and Policy, 2021)
Russia’s four largest petroleum companies, Rosneft, Surgutneftegaz, Gazprom Neft, and Lukoil, account for more than 50% of petroleum production and 70% of the demand in Russia’s drilling market. All these four petroleum companies are profoundly relaying on Foreign Direct Investments (FDI) and import of equipment and technologies. FDI have been mostly received from European Union (EU) countries and United States (U.S.) and also these countries have been major providers of equipment and technologies including technologies for offshore development, horizontal, controlled-angle, and directional drilling, hydraulic fracturing, catalysts for oil processing and petrochemicals, and geological and seismic exploration. However, since applying economic sanctions against Russia by EU and U.S. in 2014 due to Crimea annexation and Ukrainian crisis, the situation with FDI and access to technologies has been dramatically changed. Keeping with the analytical separation between economic and non-economic sanctions and using concept of political economy of energy, this paper focuses on economic energy sanctions, and for brevity refer to them as energy sanctions with emphasizes on technology export ban, foreign capital ban, state support of petroleum industry and in addition, because of the crucial role that petroleum industry plays in the Russian economy, the paper discusses the impact of both energy sanctions and COVID-19 pandemic on national economy. Keywords: Petroleum industry, Covid-19, Russia, Energy Sanctions JEL Classifications: P4, P48; Q4, Q43; K3, K32 DOI: https://doi.org/10.32479/ijeep.11385